Boron-doping-induced defect engineering enables high performance of a graphene cathode for aluminum batteries. Issue 5 (27th January 2022) - Du, Yiqun; Zhang, Boya; Kang, Rongkai; Zhou, Wei; Zhang, Wenyang; Jin, Huixin; Wan, Jiaqi; Zhang, Jianxin; Chen, Guowen
Abstract : Defect engineering using boron doping endows aluminum–graphene batteries with high capacity and outstanding long-term stability of more than 10 000 cycles. Abstract : Rechargeable aluminum batteries (RABs) have received significant interest due to the low cost, high volumetric capacity, and low flammability of aluminum. However, the paucity of reliable cathode materials poses substantial obstacles to the in-depth growth of RABs. Herein, defect engineering in virtue of boron doping is applied to the reduced graphene oxide as the cathode for RABs, endowing graphene with additional defects that improve the capacity and reaction kinetics of the electrode. Moreover, density functional theory (DFT) simulations confirm that the increased electronic conductivity, depressed diffusion barrier, and enhanced AlCl4 − adsorption ability may be ascribed to the substitution of boron for carbon. In addition, the B-doped reduced graphene oxide (BG) operates by the intercalation/de-intercalation of AlCl4 − upon the charge/discharge process. With these superior qualities, the cathode based on BG displays a high Al-storage capacity (259 mA h g −1 at 0.5 A g −1 ) and outstanding long-term stability (135 mA h g −1 at 5 A g −1 over 10 000 cycles) with a capacity decay of merely 0.0004% per cycle, one of the best performances among the state-of-the-art cathodes for RABs.